Friendship Importance Around the World: Links to Cultural Factors, Health, and Well-Being - Lu, Peiqi; Oh, Jeewon; Leahy, Katelin E.; Chopik, William J. (Frontiers in Psychology, 2021)
Prioritizing friendship is associated with many health and well-being benefits. However, to date, there have been relatively few studies that have examined cultural moderators of the link between friendship and important outcomes. In other words, is prioritizing friendships more beneficial in some contexts than others? In the current study, we examined how culture- and country-level factors were associated with the importance people place on friendships and the benefits derived from this importance. The sample comprised of 323,200 participants (M = 40.79 years, SD = 16.09 years) from ninety-nine countries from the World Values Survey. Multilevel analyses revealed that women, people with higher levels of education, and people living in countries that are more economically equal and high in indulgence placed more value on friendships. Prioritizing friendships in life was associated with better health and well-being, but these associations depended on many cultural factors. The findings are discussed in the context of the ways in which friendships can enrich health and well-being across different settings.